2014
DOI: 10.1007/s10295-014-1434-3
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid supplementation enhances urokinase production by HT-1080 cells

Abstract: Medium optimization is an important strategy that can lead to several fold increase in the production of proteins in cell culture. However, the usual methods of medium optimization are complex and time consuming. Urokinase is a widely employed thrombolytic drug for the treatment of stroke. We describe here medium optimization for maximizing urokinase production by HT-1080 cells using supplementation of specific amino acids. The new specifically designed method resulted in 240 % increase in urokinase productivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In context, the growth phase (day 1 to day 5) and the stationary phase (day 5 to day 9) of cells cultured on scaffolds were postulated from the cell proliferation analysis. Many investigators have reported that maintenance of the stationary phase results in a significant enhancement in urokinase productivity. , Moreover, successful media manipulation leads to a several-fold increase in metabolite production without creating nutrient depletion for the cells . Interestingly, uPA production from mammalian cells depends on two major factors: (i) regulation of uPA expression and (ii) addition of supplements like amino acids to enhance the uPA synthesis .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In context, the growth phase (day 1 to day 5) and the stationary phase (day 5 to day 9) of cells cultured on scaffolds were postulated from the cell proliferation analysis. Many investigators have reported that maintenance of the stationary phase results in a significant enhancement in urokinase productivity. , Moreover, successful media manipulation leads to a several-fold increase in metabolite production without creating nutrient depletion for the cells . Interestingly, uPA production from mammalian cells depends on two major factors: (i) regulation of uPA expression and (ii) addition of supplements like amino acids to enhance the uPA synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported that maintenance of the stationary phase results in a significant enhancement in urokinase productivity. , Moreover, successful media manipulation leads to a several-fold increase in metabolite production without creating nutrient depletion for the cells . Interestingly, uPA production from mammalian cells depends on two major factors: (i) regulation of uPA expression and (ii) addition of supplements like amino acids to enhance the uPA synthesis . Several studies have reported the effect of serum concentration on HT1080 cell growth and the uPA production. , On reducing the serum concentration from 10% FBS to 2% FBS, the stationary phase of the cells cultured on scaffolds was retained, which is also considered as the production phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations